Onze vriend op de pauwentroon Nederland en de laatste sjah van Iran - Warnaar, Maaike (Amsterdam University Press, 2023)
Reading the news about Iran today one can hardly imagine that relations between the Netherlands and Iran were excellent until 1979. Mohammed-Reza Pahlavi, the last shah of Persia, was known in The Netherlands as a visionary and reformer. Persia was represented as a mythical land with an ancient civilization. The Dutch royal family enjoyed visiting the shah, and large and small Dutch companies were successful in Iran. When in the 1970s awareness spread about repression under the shah, the Dutch government was faced with difficult choices. How could these relations be continued, now that public opinion had turned against it? The Dutch government decided to ignore the criticisms, and firmly held on to the idea of the shah as an enlightened despot. As such, it did not see the Iranian Revolution coming, and suffered the consequences.